THE CITY IMAGE OF SEMARAPURA (Between the Balinese Architectural Heritage and Five Exterior Elements of Modern Public Function) - Tri Adiputra, Gusti Ngurah (Widyasrama, 2015)
The city Image of Semarapura is characterized by a specific configuration of symbols, which taken as a whole permits an insight into the utility of the city. Such symbolic configurations can be taken as the outcome of the creative expression of the urban community and as such they reflect the features and the problems of this community and its components : the traumas of the past, the difficulties of the present and the expectations and hopes for the future. However, they are more than just a mirror image because urban symbolism is an essential dimension of the urban community by which its functioning is to some extents determined. This article is a report of an investigation of Semarapura city symbols in the island of Bali. The symbolic configuration of this Balinese previous provincial capital is in large measure expressed in traditional ideas about the spatial divisions of the city and its constituent parts, in statues, and in the image of the city as this is projected by authors of travel guides to Semarapura - the historian heritage. The spatial division statues and the image of the city, then, will form the subjects of the next three sections. To these is linked a conclusion about the key issues which form the foundation for the symbolism.